Efektivitas varian metode terapi komplementer untuk fatigue pada pasien penyakit paru obstruktif kronik (PPOK): Tinjauan sistematik - Gustini Putri Dewanti; I Made Kariasa; Sri Yona (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2024)
Background: The process of fighting chronic obstructive pulmonary disease (COPD) is a challenge that affects the patient's quality of life. Moreover, the inevitable symptoms of fatigue often result in limitations in physical, emotional, cognitive and social aspects. However, in overcoming this there are new opportunities, namely the use of complementary therapies to optimally treat fatigue, paving the way for more effective health care for COPD sufferers. Purpose: To investigate and synthesize scientific evidence regarding the use of complementary therapies for fatigue in COPD patients. Method: Systematic review using PRISMA guidelines using five databases, including PubMed, Scopus, ScienceDirect, Cochrane and EMBASE. Search using the keyword combination